Language in the technology subject at the Danish Higher Technical Examination Programme: Pragmatic constructivism in practice - Jeppesen, Mette Møller (Journal of Pragmatic Constructivism, 2021)
Working with problem-based learning (PBL) in the technology subject differentiates The Higher Technical Examination Programme (HTX) from other secondary school programs in Denmark. Challenges include interpretation of different elements which vary from teacher to teacher as the teachers have very different professional backgrounds. This has consequences for students and indicates that a solid disciplinary tradition has yet to be developed. It could possibly be argued that teachers’ communications on the subject, are only abstractions and not concepts. To solve these problems, it seems pertinent to apply the conceptualising method (Nørreklit 1973), to create useful and precise concepts free from possible ambiguities as a contribution to a coordinated language. In conclusion, it has been possible to use Pragmatic Constructivism (PC) to unfold the language games of the technology subject and enable the teachers to discuss their subject with each other thereby creating change in the subject and organisation.